Genetic factors predisposing to atopic dermatitis: selected genes related to the skin barrier and immune response - Nowak, Tomasz; Cieśla, Dominika (Alergologia Polska - Polish Journal of Allergology, 2025)
Atopic dermatitis (AD) is characterized by a persistent course and a complex genetic and pathophysiological basis. The development of this allergic inflammatory disease is mainly influenced by factors including predisposing genes, innate susceptibility, environmental and infectious agents, impaired structure and function of the skin barrier and immune response, abnormal colonization of the skin by microorganisms. The genes that affect the function of the epidermal barrier have been best studied in the context of AD include FLG (filaggrin) and SPINK5/LEKTI (serine protease inhibitor Kazal type 5/lymphoepithelial Kazal-type-related inhibitor). Filaggrin is responsible for binding cells in the stratum corneum of the epidermis, and mutations in its gene lead to excessive water loss and skin dryness. In turn, SPINK5 polymorphisms may result in deficiencies in the LEKTI inhibitor, leading to the activation of pro-inflammatory responses, damage to the skin barrier, and worsening of disease symptoms. The proper maintenance of the skin barrier is also influenced by kallikrein (KLK7) and STAT6 (signal transducer and activator of transcription 6). Mutations in KLK7 can lead to severe exfoliation of the epidermis, while mutations in STAT6 can contribute both to skin barrier damage and the intensification of inflammatory conditions due to increased IgE production.